Penggunaan Metode STAD untuk Meningkatkan Konsentrasi Siswa Materi Bangun Datar melalui Aplikasi Canva pada Kelas I SDN 64/I Muara Bulian - Sari, Nandita Sekar; Sartika, Hana Yuli; Syahira, Fizna; Pratama, Rd. Muhammad Deza (Lembaga Yasin AlSys, 2023)
The reduced level of student concentration and too much teacher dominance in learning results in low student learning outcomes. Analysis of the use of the STAD (Student Temas Achiefment Division) learning model through the canva application is to find out the extent to which student’s learning concentration in class I SDN 64/I Muara Bulian has increased in flat shape learning. In this study using the Classroom Action Research (PTK) type. The research was carried out in 2 cycles with 2 meetings in each cycle. Then the cubjects of this study were 27 students, consisting of 13 boys and 14 girls of class 1 SDN 64/I Muara Bulian. The data collection used is observation sheets, interviews, and document studies. Learning concentration and learning outcomes were analyzed descriptively quantitatively using the percentage technique. The results of student concentration increased from cycle I to cycle II, namely from the percentage of student completeness by 55% to 88%. It can be seen that the STAD learning model through the Canva application can increase student learning concentration in learning flat shapes.